The Role of Organizational and Individual Factors in Knowledge Management System Acceptance - Setiawan Assegaff (Bulletin of Electrical Engineering and Informatics, 2017)
The aim of this study is to investigates the how individual and organizational factors influence people behavior in using knowledge management.  This research applied Technology Acceptance Model (TAM) as a basis theory; TAM was enriched with individual and organizational factors for this study. A survey approach was conducted for data collection. Three of institutions in Banking Sector at Indonesia were invited to join this study and 215 knowledge workers were participated for the survey. Data from survey were analyzed through Structural Equations Model (SEM) using PLS (Partial Least Square) V2. The conclusion specify that ‘‘individual elements’’ and ‘‘organizational elements’’ are the significantly affect people behavior in KMS acceptance factors that influence knowledge worker behavior in knowledge sharing. However this study not found relationship between individual and organization factors and “perceived ease of use” construct with people behavior in accept KMS.